Plato's Animals : Gadflies, Horses, Swans, and Other Philosophical Beasts - Bell, Jeremy, 1977-; Naas, Michael (Book collections on Project MUSE., 2015)
Plato's Animals examines the crucial role played by animal images, metaphors, allusions, and analogies in Plato's Dialogues. These fourteen lively essays demonstrate that the gadflies, snakes, stingrays, swans, dogs, horses, and other animals that populate Plato's work are not just rhetorical embellishments. Animals are central to Plato's understanding of the hierarchy between animals, humans, and gods and are crucial to his ideas about education, sexuality, politics, aesthetics, the afterlife, the nature of the soul, and philosophy itself. The volume includes a comprehensive annotated index to Plato's bestiary in both Greek and English.